Relationship Between Midwife Support and Exclusive Breastfeeding in the Work Area of the Jamblang Health Center, Cirebon Regency - Rohemah, Emah (Riviera Publishing, 2023)
Mother's Milk is the best life fluid, containing various substances babies need. Breast milk is good for the growth and development of babies and according to their needs. Exclusive breastfeeding is only breast milk without complementary food or drink until the baby is six months old. Exclusive breastfeeding coverage at the Jamblang Community Health Center, Cirebon Regency, namely 46.3%, has yet to reach the national target of 80%. Midwife support is a factor that influences the success of exclusive breastfeeding. The purpose of this study was to determine the relationship between midwives' support and exclusive breastfeeding in the working area of the Jamblang Health Center, Cirebon Regency. This research is a qualitative descriptive survey using a cross-sectional approach. The number of respondents is 104 people. Data on midwife support and exclusive breastfeeding were obtained using a questionnaire—a statistical test to determine the relationship between variables using the chi-square test. The results of data analysis obtained a p-value of midwife support 0.038 ( p-value <0.05) for exclusive breastfeeding, meaning there is a significant relationship between midwife support for exclusive breastfeeding. Midwife have the knowledge and skills necessary to assist mothers in addressing various issues that may arise during breastfeeding. They can provide technical assistance in dealing with problems such as infant latching issues, mastitis, or insufficient breast milk production. This support can enhance the success of mothers in providing exclusive breastfeeding.